ANALYSIS OF THE EFFECTIVENESS OF IMPLEMENTATION OF STATE-OWNED ACCOUNTING MANAGEMENT INFORMATION SYSTEMS (SIMAK-BMN) IN THE ENVIRONMENT OF THE AGENCY OF FISH QUARANTINE, QUALITY CONTROL AND SAFETY OF FISHERY PRODUCTS, MINISTRY OF MARINE AND FISHERIES - Hamilah Hamilah; Amrizal Amrizal; Achmad dwi Monyko (Dinasti Publisher, 2022)
This research is based on the Stewardship theory, be the origin of the independent variable where the assessment, bookkeeping, and application of SIMAK BMN are tasks that must be fulfilled by the government as a form of optimal human resource management and making the best decisions for the benefit of the community. The purpose of this study was to determine the effect of the variables of valuation, bookkeeping, and the application of SIMAK BMN on the quality of financial reporting, which was moderated by the motivation of users of the SIMAK BMN application. 51 respondents used the purposive sampling technique from 27 work unit areas of the Ministry of Maritime Affairs and Fisheries using the SEM PLS method using the SmartPLS 3.3 software. The results showed that simultaneously and partially, the variables of assessment, bookkeeping, and the application of SIMAK BMN has a positive and significant effect on the quality of financial reporting. In contrast, users' motivation of the SIMAK BMN application can only moderate the implementation of SIMAK BMN on the quality of financial reporting. This proves that work experience alone is not enough if it is not accompanied by work motivation.